Lifestyle and Dietary Habits Affect Plasma Levels of Specific Cytokines in Healthy Subjects - D'Esposito, Vittoria; Di Tolla, Michele Francesco; Lecce, Manuela; Cavalli, Francesco; Libutti, Michele; Misso, Saverio; Cabaro, Serena; Ambrosio, Maria Rosaria; Parascandolo, Alessia; Covelli, Bianca; Perruolo, Giuseppe; Sansone, Mario; et al. (Frontiers in Nutrition, 2022)
Low-grade chronic inflammation (LGCI) is a common feature of noncommunicable diseases. Cytokines play a crucial role in LGCI. This study aimed to assess how LGCI risk factors (age, body mass index -BMI, smoke, physical activity, and diet) may impact on specific cytokine levels in a healthy population. 150 healthy volunteers were recruited and subjected to questionnaires about the last 7-days lifestyle, including smoke habit, physical activity, and food frequency. A panel of circulating cytokines, chemokines, and growth factors was analyzed by multiplex ELISA assay. BMI showed the heaviest impact on the correlation between LGCI-related risk factors and cytokines and was significantly associated with CRP levels. Aging was characterized by an increase of IL-1b, eotaxin, MCP-1, and MIP-1α. Smoking was related to higher levels of IL-1b, and CCL5/RANTES, while physical activity to MIP-1α. Within the different eating habits, CRP levels were modulated by eggs, red meat, shelled fruits, and greens consumption; however, these associations were not confirmed in a multivariate model after adjusting for BMI. Nevertheless, red meat consumption was associated with an inflammatory pattern, characterized by the increase of IL-6 and IL-8. IL-8 levels were also increased with the frequent intake of sweets, while a higher intake of shelled fruits correlated with lower levels of IL-6. Moreover, IL-6 and IL-8 formed a cluster which also included IL-1b and TNF-α. In conclusion, age, BMI, smoke, physical activity, and dietary habits are associated with specific cytokines which may represent potential markers for LGCI.